2017
DOI: 10.1177/1464884917710395
|View full text |Cite
|
Sign up to set email alerts
|

Anti-intellectualism among US students in journalism and mass communication: A cultural perspective

Abstract: This study explores how support for journalistic anti-intellectualism is condoned in the views of emerging adults in the United States as they develop attitudes toward news, audiences, and authority. Anti-rationalism and anti-elitism as cultural expressions of anti-intellectualism correlate as expected with approval of corresponding news practices. Identification with professional roles generally fails to inoculate college students against the endorsement of journalistic anti-rationalism and anti-elitism. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Misperceptions and emotional reactions reflect what people are most worried about. The public has lost trust in technology companies, academics, and the government ( McDevitt et al, 2017 ; Donovan and boyd, 2019 ). They are concerned by a dystopian future of governments tracking and controlling the public.…”
Section: Current Constructions Of Knowledge Regarding Insertable Devicesmentioning
confidence: 99%
“…Misperceptions and emotional reactions reflect what people are most worried about. The public has lost trust in technology companies, academics, and the government ( McDevitt et al, 2017 ; Donovan and boyd, 2019 ). They are concerned by a dystopian future of governments tracking and controlling the public.…”
Section: Current Constructions Of Knowledge Regarding Insertable Devicesmentioning
confidence: 99%
“…Nonetheless, xenophobia and anti-intellectualism can be found even in some of the most democratic countries, such as the UK (Bristow and Robinson, 2018) and the United States (Peters, 2018). One cause of negative attitudes towards multiculturality is the anti-intellectualism associated with right-wing K 49,7 authoritarianism and dogmatism (Eigenberger and Sealander, 2001), opposition to freedom of thought (Marques et al, 2017), anti-rationalism and populist anti-elitism (McDevitt et al, 2018) and racism and xenophobia (Bristow and Robinson, 2018). Consequently, one can argue that people who are more interested in intellectual development are also more open to multicultural diversity.…”
Section: Intellectualism Lifelong Learning and Multiculturalismmentioning
confidence: 99%
“…Moreover, several studies have shown that students are increasingly less interested in theory and expect schools and universities to provide them with more practical skills (Br atianu and V at am anescu, 2016; Bozionelos et al, 2016). This lack of intellectual curiosity and desire for knowledge has been associated with antirationalism and populist anti-elitism (McDevitt et al, 2018), less negative perceptions of cheating (Elias, 2009), right-wing authoritarianism and dogmatism (Eigenberger and Sealander, 2001) and racism and xenophobia (Bristow and Robinson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The recent decade has brought an unprecedented rise in anti-scientific and anti-intellectual movements in Western countries [ 1 , 2 ]. The trust in science and the traditional hierarchies of knowledge is declining [ 2 ], and the process can be linked to the general growth of distrust in social institutions and governments [ 3 ].…”
Section: Introductionmentioning
confidence: 99%